Embodied Harmony: The Role of Singer Body Movement in Enhancing Choral Expressivity and Ensemble Coordination - Kusumadewi , Kenya Permata (Indonesian Scientific Publication, 2024)
This study investigates the impact of singer body movement on ensemble coordination and perceived expressivity in choral performance. Grounded in theories of embodied music cognition and entrainment, the research explores how varying degrees of movement no movement, slight sway, and full body sway affect acoustic precision, synchrony, and audience evaluation. Using a within subject factorial design, 24 university level choir members performed under each movement condition. Data were collected through multi microphone recordings, OpenPose based motion tracking, and blind evaluations by expert and non expert listeners. Acoustic measures included pitch deviation, LTAS, and SPL; movement metrics captured sway amplitude and synchrony; perceptual ratings addressed expressiveness, articulation, and timing. Results indicated that slight sway consistently produced superior outcomes across all domains. Pitch deviation was lowest and movement synchrony highest under this condition. Perceptual ratings were significantly higher in slight sway than in either no movement or full body sway. Excessive movement increased pitch instability and disrupted blend, while also producing inconsistent synchronization. These findings highlight the functional role of calibrated movement in choral performance. Incorporating slight, synchronized motion can enhance ensemble cohesion and elevate audience experience without compromising acoustic integrity. The study offers empirical support for movement integrated pedagogies and suggests broader applications across ensemble types and performance genres.